Penerapan Metode Bernyanyi untuk Meningkatkan Daya Ingat Anak Usia Dini pada Materi Tanaman dan Binatang di PAUD Mutia Bunda - Dede Ridwan; Ratna Sukma Dewi; Sarmita Sarmita (Institut Madani Nusantara, 2024)
This study aimed to improve early childhood children's memory of plant and animal topics through the implementation of the singing method at PAUD Mutia Bunda. The study was motivated by children's low ability to remember the names, characteristics, and benefits of plants and animals when learning through conventional instructional methods. This research employed Classroom Action Research (CAR) based on Arikunto's model, which was conducted in two cycles consisting of the stages of planning, action, observation, and reflection. The participants were 15 Group B children aged 5–6 years during the second semester of the 2024/2025 academic year. Data were collected through oral tests, observations, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques by calculating the mean scores and the percentage of classical learning mastery in each cycle. The findings revealed that the implementation of the singing method significantly improved children's memory of plant and animal topics. The average memory score increased from 65.4 in the pre-action stage to 72.3 in Cycle I and further improved to 81.6 in Cycle II. Similarly, the percentage of classical learning mastery increased from 40% in the pre-action stage to 60% in Cycle I and reached 86.7% in Cycle II, thereby achieving the predetermined success criteria. This improvement was supported by the use of thematic songs integrated with body movements and visual media, making the learning process more engaging, concrete, and developmentally appropriate for young children. Therefore, the singing method can be considered an effective alternative thematic instructional strategy for enhancing young children's memory of learning materials related to their surrounding environment.